Public Legal Literacy and Ownership Certainty in Land Transactions in Yogyakarta: A Socio-Legal Case Study - Sari, Triana Norsita (Saneskara: Journal of Social Studies, 2025)
This study aims to analyze the level of public understanding regarding the legality of land sale transactions and its impact on the legal certainty of ownership. The focus is directed toward examining the extent to which low legal literacy contributes to the continuation of such practices and how it affects social and economic stability. The study employs a qualitative case study design conducted in Yogyakarta. Data were collected through in-depth interviews with community members, Land Deed Officials (PPAT)/Notaries, and local Land Office authorities, supported by documentation analysis of sale deeds, land certificates, and court decisions. Data analysis involved reduction, descriptive presentation, and conclusion drawing, while validity was ensured through source and theoretical triangulation. The results indicate that informal land sale practices significantly weaken legal certainty, reduce the economic value of land, and potentially trigger social conflicts. Low legal awareness emerged as the main factor driving communities to avoid formal procedures, often perceived as costly, complicated, and time-consuming. The role of PPAT and Land Offices is therefore crucial, not only in administrative functions but also as agents of legal and social education. The findings highlight the importance of a socio-legal approach that integrates law enforcement with community education to enhance legal awareness. Recommendations include establishing community-based land law clinics, utilizing digital platforms for legal outreach, and reforming land registration bureaucracy. However, the study is limited to a specific regional context, which restricts the generalizability of findings to other areas with different socio-cultural conditions, thus requiring further research.